STRATEGI PEMASARAN KOPI BIJI SALAK â€œKOBISAâ€ DI DESA PANGU KECAMATAN RA-TAHAN TIMUR KABUPATEN MINAHASA TENGGARA - Gabriella F. Ompi; Caroline B.D. Pakasi; Nortje M. Benu (Universitas Sam Ratulangi, 2016)
ABSTRACTSoutheast Minahasa Regency, one of the areas in North Sulawesi is a region with a leading sectors namely agriculture sector. Subdistrict Ratahan East is one of the districts in Southeast Minahasa Regency is known as a regional fruit